2016
DOI: 10.1038/mp.2015.206
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual convergence: increased inflammation is associated with increased basal ganglia glutamate in patients with major depression

Abstract: Inflammation and altered glutamate metabolism are two pathways implicated in the pathophysiology of depression. Interestingly, these pathways may be linked given that administration of inflammatory cytokines such as interferon-α to otherwise non-depressed controls increased glutamate in the basal ganglia and dorsal anterior cingulate cortex (dACC) as measured by magnetic resonance spectroscopy (MRS). Whether increased inflammation is associated with increased glutamate among patients with major depression is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(159 citation statements)
references
References 73 publications
(97 reference statements)
10
147
1
1
Order By: Relevance
“…A recent study showed that elevated Glu in the ACC associated with BD patients in euthymic states was related to number of depressive/manic episodes (21); notably, this finding may allow for differentiation of depression between BD and MDD. Impaired oxidative metabolism in glutamatergic neurons has been hypothesized to explain elevated Glx and lactate levels associated with mixed or depressed states in BD (33), and further supports a contributory role of inflammation in the pathophysiology of depression (34). Wide and overlapping ranges of mood and neurocognitive states in BD (35) increase variation within and between study samples, contributing to challenges in interpreting neurochemical and functional imaging studies of BD.…”
Section: Dysregulation Of Glutamatergic and Gabaergic Neurotransmissimentioning
confidence: 83%
“…A recent study showed that elevated Glu in the ACC associated with BD patients in euthymic states was related to number of depressive/manic episodes (21); notably, this finding may allow for differentiation of depression between BD and MDD. Impaired oxidative metabolism in glutamatergic neurons has been hypothesized to explain elevated Glx and lactate levels associated with mixed or depressed states in BD (33), and further supports a contributory role of inflammation in the pathophysiology of depression (34). Wide and overlapping ranges of mood and neurocognitive states in BD (35) increase variation within and between study samples, contributing to challenges in interpreting neurochemical and functional imaging studies of BD.…”
Section: Dysregulation Of Glutamatergic and Gabaergic Neurotransmissimentioning
confidence: 83%
“…Although mood disorders may have complex pathophysiology with heterogeneous etiologies, it is thought that increased inflammation may be involved in the disease process and contribute to discreet symptomologies in a subset of patients. Indeed, recent studies have indicated that high inflammation (plasma CRP concentrations 43 mg/l, as defined by the American Heart Association; Ridker, 2003) is consistently found in 20-40% of patients with MDD, with higher concentrations observed in patients who are resistant to standard antidepressant therapies Haroon et al, 2016;Raison et al, 2013a;Raison et al, 2013b;Rapaport et al, 2016). Similar increases in inflammatory cytokines and acute-phase reactants have also been reported in patients with bipolar disorder and schizophrenia, including meta-analyses (Goldsmith et al, 2016b;Miller et al, 2011;Potvin et al, 2008).…”
Section: Increased Inflammation In Psychiatric Disordersmentioning
confidence: 87%
“…For example, in patients from a high-risk urban setting with a history of trauma, those who carried a CRP genotype (rs1130864) that is associated with elevated CRP concentrations had higher rates of posttraumatic stress disorder and reported higher scores for the loss of interest in activities (Michopoulos et al, 2015). Furthermore, recent data indicate that increased plasma concentrations of CRP and inflammatory cytokines and their soluble receptors correlate with symptoms of both anhedonia and psychomotor slowing in medically stable patients with MDD Goldsmith et al, 2016a;Haroon et al, 2016). These findings provide encouraging data that increased inflammation may be associated with symptoms of motivation and motor behavior across disorders, and may be useful for identifying subtypes of patients with psychiatric illness.…”
Section: Inflammation-induced Impairments In Motivation and Motor Actmentioning
confidence: 99%
“…In their study using 18F-DOPA PET Martinot et al [86] demonstrated a reduction in left caudate tracer uptake in MDD patients with psychomotor retardation but not MDD patients with high impulsivity or comparison control participants, providing direct evidence of a link between striatal dopamine hypofunction and psychomotor retardation. The importance of the left dorsal striatum to psychomotor retardation associated with MDD and inflammation has been further strengthened by a recent paper demonstrating a link between plasma and CSF levels of C-reactive protein (CRP), left basal ganglia glutamate, and psychomotor slowing in untreated depressed patients [89].…”
Section: Psychomotor Retardationmentioning
confidence: 99%